2021
DOI: 10.47723/kcmj.v17i1.294
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency/ insufficiency and some of its related factors in a sample of Iraqi pregnant women and their neonates at Al-Elwiya Maternity Teaching Hospital during 2019

Abstract: Background: Vitamin D deficiency/ insufficiency is common in different age groups in both genders especially among pregnant women and neonates where it is associated with several adverse outcomes including preeclampsia and preterm delivery.   Objectives: To assess the extent of vitamin D deficiency/ insufficiency among mothers and their neonates and some factors related to it and identify some adverse outcomes of the deficiency/ insufficiency on neonates (preterm birth and low birth weight). Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In our study, there were more newborn boys than girls. The majority of mothers had significant vitamin D deficiencies, which is similar to earlier studies (12)(13)(14)(15)(16) and other nations, where deficiencies have been reported to affect 81% of expectant mothers in Nepal (17) , over 90% in Guizhou, China (18) , and Saudi Arabia (19) . Nearly 44% of mothers and babies were found to have the condition, according to a study's pooled findings across African nations (20) .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, there were more newborn boys than girls. The majority of mothers had significant vitamin D deficiencies, which is similar to earlier studies (12)(13)(14)(15)(16) and other nations, where deficiencies have been reported to affect 81% of expectant mothers in Nepal (17) , over 90% in Guizhou, China (18) , and Saudi Arabia (19) . Nearly 44% of mothers and babies were found to have the condition, according to a study's pooled findings across African nations (20) .…”
Section: Discussionsupporting
confidence: 89%
“…However, when measured, it was found to be low in the majority of participants (12.28 ng/mL ± 5.2). Keeping in mind that vitamin D 3 deficiency is a worldwide problem [ 34 38 ], this group reflected the actual vitamin D 3 level in the general population. Although serum calcium and phosphate level were low in the CG, they were still within the normal range.…”
Section: Discussionmentioning
confidence: 99%